Little houses [book with audioplayer] - Henkes, Kevin ([Library of Ideas, LLC], 2023)
A young girl visiting her grandparents at the beach stays in a little house and walks along the shore gathering seashells, wondering about the creatures who used to live in each shell, about the hidden treasures of the sea--and about the world.